Remaking the Democratic Party : Lyndon B. Johnson as a native-son presidential candidate - Walton, Hanes, Jr., 1941-2013; Ford, Pearl K., 1972-; Allen, Josephine A. V. (University of Michigan Press, 2016)
A continuation of Hanes Walton Jr.'s work on Southern Democratic presidents, Remaking the Democratic Party analyzes the congressional and presidential elections of Lyndon Baines Johnson. This study builds upon the general theory of the native-son phenomenon to demonstrate that a Southern native-son can win the presidency without the localism evident in the elections of Bill Clinton and Jimmy Carter. Although ridiculed by contemporaries for his apparent lack of control over formal party politics and the national committee, Johnson excelled at leading the Democratic Party's policy agenda. While a senator and as president, Johnson advocated for-and secured-liberal social welfare and civil rights legislation, forcing the party to break with its Southern tradition of elitism, conservatism, and white supremacy. In a way, Johnson set the terms for the continuing partisan battle because, by countering the Democrats' new ideology, the Republican Party also underwent a transformation.